Does the Hebrew Bible have anything to tell us about HIV/AIDS? - Stiebert, Johanna (Missionalia: Southern African Journal of Mission Studies, 2001)
Even though the Hebrew Bible tells us nothing directly about HIV/AIDS it is used by many people as a source of authority on contemporary ethical issues and therefore it is important to see what it does say about illness, health and healing.
Free